(untitled) (Jurnal Elektronika dan Telekomunikasi, 2021)
This study aims to evaluate the structural, magnetic, and microwave absorbing properties at the X-band region of oxidized mill scales as by-product derived from a steel making process by means of a facile solid-state reaction. The oxidized mill scales were heated at 600 °C for 4 h followed by mixing with NiO. A calcination process took place at 900 °C and sintering process were conducted at 1260 °C with a milling process conducted in between the heating process. X-ray diffraction (XRD) and scanning electron microscope (SEM) equipped with energy dispersive spectrometer (EDS) were employed to evaluate the structural properties of the Ni-ferrites samples. Remacomp measurement were conducted to evaluate the magnetic properties and vector network analyzer (VNA) to measure its microwave properties. A single phase of NiFe2O4 was confirmed by XRD data. The site occupancies derived from the Rietveld refinement shows that the Ni:Fe:O ratio deviates from the 1:2:4 ratio as that suggests vacancies formed in the Ni2+ and Fe3+ that lowers the unit cell density to 5.08 g/cm3 that further confirmed by EDS measurement. The coercivity of 11 kOe is also higher than the bulk NiFe2O4¬ prepared by the chemical grade raw materials. The reflection data of the microwave properties at X-band of 8-12 GHz do not shows significant absorptions. This study suggests that the selected preparation method yields a single phase, however with the significant crystallographic defects and has less ‘soft’ magnetic properties compared to NiFe2O4 prepared using chemical grade by previous study.